Procedure in negotiation amounts in construction project disputes - Sa'adon, Suhaili (2013)
Construction disputes can often be resolved using several techniques including the purpose of negotiation, mediation, dispute resolution boards, arbitration, and litigation. Negotiation is considered the most preferred technique due to the following facts; first it prevents litigation amongst project parties, and second it keeps a harmonious relationship between project participants. Further, negotiation saves the time, expenses and efforts that are associated with other resolutions techniques. The purpose of this paper is to provide a tool that is geared towards assisting construction contractors during negotiation process. Therefore, research methodology for the modules capture the main characteristics of the negotiation process including; the expected claim duration in the case of litigation, certainty of litigation, and contractor’s intention to make litigation. The objective of this paper also described the associated factors affecting of these modules and their negotiation approaches in dispute resolution which have been determined based on interviews with claims’ experts and questionnaire surveys. Analytical hierarchy process and utility theory are used to determine weights and utility values of attributes, respectively. Decision an analysis is used to estimate the equivalent monetary value of litigation. Hence, the findings from a case study are presented to illustrate the practical use of the proposed procedure in negotiation and its ability to determine the minimum acceptable claim amount. Consequently, research limitations are the knowledge of the negotiation was retrieved from the Johor Bahru construction industry. However, the utilized methodology can be applied to capture local contraction practices, law and politics in other construction industries. Thus, the value from this research presents a negotiation that is developed to assist contractors in calculating the lower threshold of a claim value, which can be considered, during construction disputes process with owners